Análisis jurisprudencial de la mano invisible de Adam Smith en la economía social de mercado peruana - Ahomed Chávez, Omar Abraham (2022)
The present scientific work seeks to analyze through cases law the scope of the invisible hand within the social market economy. The specific topic of the investigation is about the balance that could exist between state intervention and free enterprise. To do this, we will develop as a theoretical framework on free trade and state interventionism and the principle of proportionality; in the conceptual framework, we will address the invisible hand and the Peruvian constitutional norms that regulate state intervention in the market economy. Then we will study the cases law of the Constitutional Court of Peru where there was a conflict between state planning and market freedom and the invisible hand of Adam Smith.